The Effectiveness of Using Conversational Video-Based Learning to Increase Vocabulary Mastery - Ananta, Bian Selviana; Agustina, Ria Kamilah (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
This research aimed to find out the effectiveness of using Conversational Video-based Learning to increase Students’ vocabulary mastery. It used Pre-Experimental Design with one group pre-test and post-test design. the 7th grade E students’ academic year 2023-2024 SMP A. Wahid Hasyim Tebuireng, Jombang with a total of 32 students. The result showed that vocabulary of SMP A. Wahid Hasyim was still considered lacking with mean score of the pre-test is 53,5938. After being treatment, the students’ vocabulary is increased after using Conversational Video-based learning with the mean score of the post-test 77,34375. There is significant difference between Students’ vocabulary mastery before and after being taught by using Conversational Video-based Learning. By using descriptive analysis test, the normality test, and the Paired Samples Test showed that a significant value (2-tailed) of 0.000 the data are less than (<0.05) so it can be said that the meaning that H0 is rejected and H1 is accepted. In short, this means that conversational video-based learning as the media is effectively applied in improving students' vocabulary mastery at SMP A. Wahid Hasyim Tebuireng Jombang.